QR Code-Based Ordering and Reservation System Design to Improve Cafe Operational Efficiency - Berlian Putri Zezar; Anna Dina Kalifia (Komunitas Dosen Indonesia, 2025)
The increasing demand for service efficiency and digital interaction in the food and beverage industry has driven businesses to adopt technological innovations that streamline ordering processes. Manual order-taking often results in long queues, inaccurate recording, and reduced customer satisfaction, emphasizing the need for digital transformation. This study aims to design and implement a QR Code-based ordering and reservation system that enhances operational efficiency and minimizes human error in café service management. The research employs a Prototyping development method consisting of five stages: data collection, system requirement analysis, interface design, prototype implementation, and functional testing. The system is developed as a web-based application that allows customers to place orders and make reservations independently through QR Code scanning. Testing results show that the system functions effectively across all core features, reducing customer waiting time and eliminating manual recording errors. The integrated reservation feature also improves table management and staff coordination. Unlike most prior QR Code-based systems that focus only on menu ordering, this study introduces an integrated, responsive web platform combining ordering and reservation in a unified workflow. The developed prototype addresses inefficiencies in manual service operations while demonstrating measurable improvements in speed, accuracy, and user satisfaction. This integration represents the main contribution of the research, providing a distinctive model for enhancing digital café operations through user-centered design. The study contributes to the advancement of digital ordering systems and offers both practical and academic implications for future F&B digitalization initiatives